P–192 Efficacy of postponement of intracytoplasmic sperm injection timing after spindle visualization for Metaphase I oocytes. (6th August 2021) - Hisa, N; Ito, H; Kotake, R; Akimoto, S; Suzuki, Y; Takahashi, Y; Igarashi, C; Ono, S; Harada, H; Nakata, M; Abe, T
Abstract: Study question: Does postponement of intracytoplasmic sperm injection (ICSI) timing after spindle visualization for Metaphase I (MI) oocytes improve developmental outcomes of embryos? Summary answer: Postponement of ICSI timing after spindle visualization for MI oocytes improves blastocyst utility rates. What is known already: Immature oocytes are generally considered poor developmental outcomes. Meanwhile, the timing of ICSI adjusted by using spindle visualization can improve clinically utilized embryos and live birth rates, but these outcomes remain inferior to those of mature oocytes. In in vitro maturation culture, nuclear maturation is thought to occur before the completion of cytoplasmic maturation, and in immature oocytes, synchronization of nuclear and cytoplasmic maturation may be insufficient for ICSI immediately after spindle visualization. Study design, size, duration: Data for this retrospective cohort study were obtained 672 oocytes retrieved under mild stimulation cycles using letrozole, in patients aged younger than 39 years between April 2017 and October 2020.Written informed consent was obtained from all patients. This study was approved by the institutional review board. Participants/materials, setting, methods: As a control group, 464 MetaphaseIIoocytes that underwent ICSI immediately after visualization of the spindle were used. In group A, 103 MI oocytes underwent ICSI immediately after the first polar body release and spindle visualization, and in group B, 105 oocytes underwent ICSI 2–3 hours after spindle visualization. The primary outcomes were fertilization rates, degeneration, cleavage, embryo blastocyst formation, and utility rates. Outcomes were compared among the three groups. Main results and the role of chance: The baseline fertilization rates of each group (control, A, B) were 82.3% (382/464), 73.8% (76/103), and 83.8% (88/105), respectively. The rate was significantly lower in group A than in the control group (P < 0.05), and also tended to be lower in group A than in group B, although the difference was not significant. There was no significant difference in abnormal fertilization rates, oocyte degeneration rates, cleavage rates, and blastocyst formation rates among the three groups. [control, A, B: abnormal fertilization rate: 4.3% (20/464), 8.7% (9/103), 4.8% (5/105); oocyte degeneration rates: 3.0% (14/464), 1.9% (2/103), 3.8% (4/105); cleavage rates: 95.6% (307/321), 93.8% (61/65), 98.7% (74/75); blastocyst formation rates: 58.6% (177/302), 51.7% (31/60), 55.4% (41/74), respectively]. The blastocyst utility rates of control group and group B were significantly higher than in group A [41.7% (126/302), 45.9% (34/74), 26.7% (16/60), respectively] (P < 0.05). There were no significantly different outcomes between the control group and group B. Limitations, reasons for caution: The optimal timing of ICSI for MI oocyte cannot be determined by the presence or absence of spindles. In addition, the postponement duration we set was based on reports which reported on final oocyte maturation, and further investigation is needed to establish the optimal ICSI timing for MI oocytes. Wider implications of the findings: In MI oocytes, postponement of ICSI timing after spindle visualization is essential for synchronization of the nucleus and cytoplasmic maturation. Trial registration number: none